RESPON PERTUMBUHAN TANAMAN KEDELAI (Glycine max L. Merril) DENGAN PEMBERIAN POC LIMBAH IKAN DAN SOLID - Turmanto Turmanto; Yusmaidar Sepriani; Khairul Rizal (JURNAL AGROPLASMA, 2021)
Soybean is an important food crop after rice and maize. Soybean production in East Kalimantan based on the estimated 2014 rate is estimated at 1,263 tons of dry seeds. Compared to 2013 production there was a decrease of 139 tons (9.91%) (BPS, 2014). The low productivity is because soybean cultivation is still not optimal. One of the cultivation that can be done is by using Fish Waste and Solid POC. The purpose of this study was to determine the growth response of soybean (Glycine max l. Merril) by giving poc fish waste and solids. This research was conducted in Sidorejo Hamlet, Bilah Hilir District, Labuhan Batu Regency, North Sumatra Province. The research method used was factorial randomized block design (RBD) consisting of 2 factors, 9 combinations and 3 replications. The first factor was the provision of POC fish waste (P) consisting of 3 levels, namely: P0 = 0 ml / planting hole, P1 = 100 ml / planting hole, P2 = 200 ml / planting hole. The second factor is the provision of solid (S) consisting of 3 levels, namely: S0 = 0 ml / planting hole, S1: 100 ml / planting hole, S2: 200 ml / planting hole. Parameters observed were plant height, number of leaves, leaf width and stem diameter. Based on the results of research in the field, it shows that the provision of fish waste poc and solid has no significant effect on all observed parameters. Meanwhile, the interaction between poc and solid fish waste also had no significant effect on all observed parameters. Keywords: Soybean, POC Fish Waste, and Solid